2014
DOI: 10.28945/1963
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of International Information Security Regulations

Abstract: Information security regulation is coming of age, with regulation very recently being passed in emerging economies. Developed nations have stable regulation, whose implementation and effectiveness can now be evaluated. This paper evaluates security regulation across both these developed and emerging economies, across four continents and six nations: China, India, Indonesia, Brazil, Germany, and the United States. We find national security regulations may be comprehensive or piecemeal; strategic or tactical in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Many countries in the world still are without sufficient regulation and/or enforcement to protect user's data and privacy [22], the author analyzed the existing security systems in Ugandan Universities. According to [10], [21],) Information security works under the principles of confidentiality, integrity and availability.…”
Section: Research Questionmentioning
confidence: 99%
“…Many countries in the world still are without sufficient regulation and/or enforcement to protect user's data and privacy [22], the author analyzed the existing security systems in Ugandan Universities. According to [10], [21],) Information security works under the principles of confidentiality, integrity and availability.…”
Section: Research Questionmentioning
confidence: 99%
“…Some countries' regulations refer to security goals, while others specify detailed implementations in their regulations. Some nations simply establish security goals, while others require risk management [10]-the combination of all the above supporting the decisions with the compliance strategy.…”
Section: Case Studymentioning
confidence: 99%
“…An analysis of the regulation of information security at the state level in economically developed countries, performed in [3], revealed that the safety rules may be comprehensive or partial, strategic or tactical, reactive or proactive. Some countries define security goals only; others have efficient mechanisms of risk management in this area.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%